Promoting Independence in Dementia – Changing Lifestyles & Improving Outcomes: RE-AIM Study of The PRIDE Self-Management App - Lee, Abigail Rebecca (2023)
Introduction: The ever-increasing prevalence of dementia globally is placing significant demands on health and social care sectors and on families. Given the progressive nature of dementia, self-management can support people and their families to optimise the level of autonomy and independence they are capable of and reduce excess disability. Incorporating technology into self-management interventions could help remove geographical barriers and enable services to deliver to a wider-reaching audience.